UnitJudge: a novel online automatic correction system for long programming practices by means of unit tests - Garcia-Magarino, Ivan; Pita, Isabel; Arroyo, Javier; Fernandez, Marta Lopez; Bravo-Agapito, Javier; Segura, Clara; Gilaberte, Raquel Lacuesta (2023 10th International and the 16th National Conference on E-Learning and E-Teaching (ICeLeT), 2023)
Existing online judge systems for automatically evaluating programming exercises mainly rely on standard input and output streams without considering small pieces of code such as functions, methods or classes. This approach qualifies for short programming exercises in which input and outputs are clearly indicated. However, these kinds of judges are hard to apply in long programming exercises. This article presents a novel online judge system called UnitJudge designed for evaluating long programming practices based on unit testing for small pieces of the practice. In the experiments on two long practices about the game of the Goose in Fundamentals of Programming subject the first year of the Double Grade of Computer Science and Mathematics and the Grade of Data Engineer and Artificial Intelligence in Complutense University of Madrid, students perceived UnitJudge useful (5.62 out of 7) and easy to learn (5.99 out of 7) according to the Usefulness, Satisfaction and Ease of use validated scale.